Application of biomass from the microalgae Chlorella sp. as biofertilizer in the cultivation of Raphanus sativus L. (Research, Society and Development, 2024)
The radish (Raphanus sativus L.) stores a significant percentage of nutrients present in the soil in its root, due to its nature as a tuberous vegetable. This plant is highly demanding in nutritional terms and has a short growth cycle. It is crucial to implement proper management, using appropriate techniques to meet your needs. Organic fertilizer appears as a sustainable and low-cost alternative for producers, contributing to the reduction of environmental impacts and minimizing the use of chemical products. Thus, the present study aims to evaluate the development of radish cultivated with microalgae biomass Chlorella sp., investigating the viability of microalgae as biofertilizers in agriculture. Four treatments were carried out, involving chemical fertilizer and different concentrations of algal biomass. The parameters analyzed included fresh biomass (BM), dry biomass (BC), shoot (PA), fresh biomass (BF), tuberous root (RT), taproot length (CRP), tuberous root diameter (DRT) and total plant height (ATP). None of the treatments presented statistically significant results, not allowing the affirmation of the potential applicability of microalgae as biofertilizers in radish cultivation.